Construction of Computer Experiment Designs from Marked Point Processes - Ahmed AIT AMEUR , Hichem ELMOSSAOUI , Nadia OUKID (Utilitas Mathematica, 2024)
This article presents a method for constructing computer experiment designs. This methodis based on the theory of stochastic processes, particularly two-type marked point processes. The designs obtained using the Monte Carlo Markov Chain (MCMC) method and the Metropolis-Hastings algorithm are highly adaptable and can, therefore, address various objectives. A detailed study on the convergence of the Markov chain has been conducted. A comparison between our approach and other existing Computer designs has been performed.